Nickel doped nanohydroxyapatite: vascular endothelial growth factor inducing biomaterial for bone tissue engineering1. Issue 89 (27th September 2015) - Anu Priya, B.; Senthilguru, K.; Agarwal, T.; Gautham Hari Narayana, S. N.; Giri, S.; Pramanik, K.; Pal, K.; Banerjee, I.
<x xml:space="preserve">Abstract</x> Biomaterial induced activation of vascular endothelial growth factor (VEGF) pathway for angiogenesis is now gaining recognition as an effective option for tissue engineering.